The effectiveness of the PMS used for middle-level managers in the SAMHS HQ within Gauteng Province - Dube, Boitumelo Joyce (My University, 2014)
Performance Management (PM) is one of the most important formal management tools that organisations use in the evaluation of individual job performances and potential. The organisation uses this tool to arrive at human resource decisions that further the goals of the individual and the organisation. The purpose of this descriptive quantitative study was to investigate the effectiveness of the Public Management Systems (PMS) used for middlelevel managers in the SA Military Health Services (SAMHS) Headquarters in Gauteng Province. A self-administered questionnaire was used to collect data. Microsoft Excel statistics functions were used to calculate the totals, produce tables, graphs, and pie charts. The main finding of the study was that “an effective PMS could be implemented fruitfully if the emphasis is on proper implementation”. It was established that although much momentum has been gained with the implementation of the PMS in the SAMHS HQ critical issues such as communication, performance reviews, and performance reward need to be addressed by management.
Thesis (M.M. (Security))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2013.
Keywords: Performance management; Job performance; Evaluation; SA Military Health Services; South Africa